2004
DOI: 10.1002/bdra.20000
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoglycemia induced changes in cell death and cell proliferation in the organogenesis stage embryonic mouse heart

Abstract: Hypoglycemia reduces embryonic viability, induces significant cell death, and reduces cell proliferation in the E9.5 mouse heart, and these processes may involve active caspase-3 and p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
1
0
0
Order By: Relevance
“…After dewaxing, Hoechst-stained nuclei were imaged using a DAPI/Hoechst/ AMA filter cube (excitation, 360 nm; emission, 469 nm; Chroma) and LysoTracker was detected with a G2A cube. As reported in other studies (Ghatnekar et al, 2004;Zucker et al, 1999), pilot experiments in B6CBA/J F2 conceptuses confirmed the specificity of LysoTracker Red uptake. Briefly, apoptotic cells were detected in B6CBA/J F2 conceptuses primarily within the neurectoderm (LB to LHF stages), with a few positive cells in the allantoic core (data not shown).…”
Section: Lysotracker Red Stainingsupporting
confidence: 87%
“…After dewaxing, Hoechst-stained nuclei were imaged using a DAPI/Hoechst/ AMA filter cube (excitation, 360 nm; emission, 469 nm; Chroma) and LysoTracker was detected with a G2A cube. As reported in other studies (Ghatnekar et al, 2004;Zucker et al, 1999), pilot experiments in B6CBA/J F2 conceptuses confirmed the specificity of LysoTracker Red uptake. Briefly, apoptotic cells were detected in B6CBA/J F2 conceptuses primarily within the neurectoderm (LB to LHF stages), with a few positive cells in the allantoic core (data not shown).…”
Section: Lysotracker Red Stainingsupporting
confidence: 87%